microRNA-140 Regulates PDGFRα and Is Involved in Adipocyte Differentiation - Yan, Yi; Yuan, Jiahui; Luo, Xiaomao; Yu, Xiuju; Lu, Jiayin; Hou, Wei; He, Xiaoyan; Zhang, Liping; Cao, Jing; Wang, Haidong (Frontiers in Molecular Biosciences, 2022)
In recent years, the studies of the role of microRNAs in adipogenesis and adipocyte development. and the corresponding molecular mechanism have received wide attention. In this work, we investigated the function of miR-140 in the process of adipogenesis and the molecular pathways involved, and we found that adipogenic treatment promoted miR-140-5p RNA level in preadipocyte. Over-expression of miR-140-5p in preadipocytes accelerated lipogenesis along with adipogenic differentiation by transcriptional modulation of adipogenesis-linked genes. In the meanwhile, silencing endogenous miR-140-5p dampened adipogenesis. Platelet-derived growth factor receptor alpha (PDGFR) was shown to be a miR-140-5p target gene. miR-140-5p over-expression in preadipocyte 3T3-L1 diminished PDGFR expression, but silencing of miR-140-5p augmented it. In addition, over-expression of PDGFRα suppressed adipogenic differentiation and lipogenesis, while its knockdown enhanced these biological processes of preadipocyte 3T3-L1. Altogether, our current findings reveal that miR-140-5p induces lipogenesis and adipogenic differentiation in 3T3-L1 cells by targeting PDGFRα, therefore regulating adipogenesis. Our research provides molecular targets and theoretical basis for the treatment of obesity-related metabolic diseases.